The impact of innovative glucose-lowering drugs on the course and outcome of COVID-19 in patients with type 2 diabetes mellitus - T. N. Markova; M. S. Stas (Сахарный диабет)
Patients with type 2 diabetes mellitus (T2DM) are at high risk of adverse outcomes in coronavirus infection (COVID-19). Despite the gradual resolution of the pandemic, new strains of the virus are emerging, characterized by high contagiousness, and the risk of infection becoming a seasonal disease is increasing. In this connection, the issue of identifying risk factors that aggravate the course of COVID-19 in patients with T2DM, including the role of initial hypoglycemic therapy, remains relevant.The review presents and systematizes up-to-date information (according to randomized clinical trials and meta-analyses) on the effect of outpatient and inpatient use of metformin and innovative hypoglycemic drugs (glucagon-like peptide-1 receptor agonists, sodium-glucose cotransporter-2 inhibitors, dipeptidyl peptidase-4 inhibitors) on the course and outcome of COVID-19 in patients with T2DM. At the same time, the potential mechanisms of the pathogenetic effect of drugs on the course of COVID-19, positive and negative aspects of their administration are described.